2016
DOI: 10.1007/s00453-016-0259-z
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized and Approximation Algorithms for the Load Coloring Problem

Abstract: Let c, k be two positive integers. Given a graph G = (V, E), the c-Load Coloring problem asks whether there is a c-coloring ϕ : V → [c] such that for every i ∈ [c], there are at least k edges with both endvertices colored i. Gutin and Jones (Inf Process Lett 114:446-449, 2014) studied this problem with c = 2. They showed 2-Load Coloring to be fixed-parameter tractable (FPT) with parameter k by obtaining a kernel with at most 7k vertices. In this paper, we extend the study to any fixed c by giving both a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Finally, let us also mention the min c-judicious partitioning (which is a maximization problem), called c-Load Coloring, where given a graph G and a positive integer k, the goal is to decide whether V (G) can be partitioned into c parts so that each part has at least k edges. Barbero et al [2] showed that this problem is FPT (also see [21]).…”
Section: Balanced Judicious Bipartition (Bjb)mentioning
confidence: 97%
“…Finally, let us also mention the min c-judicious partitioning (which is a maximization problem), called c-Load Coloring, where given a graph G and a positive integer k, the goal is to decide whether V (G) can be partitioned into c parts so that each part has at least k edges. Barbero et al [2] showed that this problem is FPT (also see [21]).…”
Section: Balanced Judicious Bipartition (Bjb)mentioning
confidence: 97%
“…In [6,7], the parameterized and approximation algorithms are proposed to solve the load coloring problem, and theoretically prove their capability in finding the best solution. On the other hand, considering the theoretical intractability of MLCP, several heuristic algorithms are proposed to find the best solutions.…”
Section: Related Workmentioning
confidence: 99%
“…Gutin et al [9] proved that the problem admits a polynomial kernel (with at most 7k vertices) parameterized by k. They also showed that the problem is fixed-parameter tractable when parameterized by the tree-width of the input graph. More recently, Barbero et al [2] obtained a kernel for the problem with at most 4k vertices improving the result of [9].…”
Section: Introductionmentioning
confidence: 98%